4-(27-3)=x-(13-4)
4 - 24=x-9
4+(-24)=x-9
-(24-4)=x-9
-20=x-9
x=(-20)+9
x= - (20-9)
x= - 11
Đúng 0
Bình luận (0)
4-(27-3)=x-(13-4)
4 - 24=x-9
4+(-24)=x-9
-(24-4)=x-9
-20=x-9
x=(-20)+9
x= - (20-9)
x= - 11
Tìm số nguyên x, biết 4 – (27 - 3) = x – (13 - 4).
Tìm số nguyên x, biết: 4 - (27-3) = x - (13-4)
Tìm số nguyên x, biết : 4-(27-3) =x-(13-4)
tìm số nguyên x biết 4-[27-3]=x-[13-4]
Tìm số nguyên x, biết : 4 -(27 - 3) = x - (13-4)
Tìm số nguyên x ,biết:4 - (27-3)=x - (13-4)
tìm số nguyên x , biết : 4 - ( 27 - 3 ) = x - ( 13 - 4 )
Tìm số nguyên x biết :
4- ( 27-3 ) = x - ( 13 - 4 )
Tìm số nguyên x , biết :
4-(27-3)=x-(13-4 )